Prevalencia de malaria en la población de la comunidad de Santa Clara del Distrito de San Juan, Región Loreto - Perú 2018. - Chuquipiondo Laulate, Gladys Nahir (2019)
PREVALENCE OF MALARIA IN THE SANTA CLARA COMMUNITY OF San Juan DISTRICT, REGION LORETO-PERU 2018. The purpose of this research was to determine the prevalence of malaria in the population of the Santa Clara community as a Public Health problem in the Health Post "Santa Clara of Nanay I-3" Regional Office of Loreto, during the period 2018; due to the reemergence of infectious diseases transmitted by the vector that were believed to be controlled or eradicated. Objective: To determine the prevalence of malaria in the population of Santa Clara community in the San Juan district, Loreto region 2018. Methodology: The present study is Basic-descriptive. Monitoring of all the samples requested and of the results is carried out in order to analyze the data and the species for a period of one year. Results: A total of 4592 cases of malaria were obtained in the Santa Clara community during the period 2018. Of the four species of Plasmodium, two species were diagnosed and the highest incidence of infection was by Plasmodium vivax with 907 cases, the number of cases being 19.8%. In lower incidence it is for Plasmodium falciparum registering 119 throughout the year, which represents 2.6%. Finally we observed 10 cases of infection caused by both species at the same time being mixed cases with minimum incidence of 0.22%. Conclusions: The highest incidence of malaria prevalence in the Santa Clara community is due to infection of Plasmodium vivax with 19.8%. In lower incidence is Plasmodium falciparum with 2.6%. In minimal incidence is caused by both species at the same time being cases of mixed infection in 0.22%. The total of positive thick drop in patients is equivalent to 22.6 %.